Determinants of Capital Structure: Evidence from UK Listed Company Panel Data - Trinh, Ngoc Luong (2012)
This paper investigates the determinants of the UK listed company capital structure and their impacts on different debt maturity. The analysis was carried out using a panel data set of 230 non-financial companies in the FTSE 350 index from 2002 to 2011. In addition, a set of 6 theoretical determinants as outlined by existing literature including: asset structure, firm size, growth opportunities, profitability, liquidity and non-debt tax shields was used to test their relationships with different debt measures. In addition, one-way ANOVA analysis is adopted to test the effect of industry classification on the firm leverage. The results show that asset structure, firm size, growth opportunities and non-debt tax shields are negatively related to leverage while profitability and liquidity are positively correlated with leverage. The empirical evidence hence fails to reasonably support a specific capital structure theory which can fully explain the UK corporate financing decisions. Thus we believe that a dynamic model which can incorporate both components of trade-off and pecking order theory would provide a fruitful justification not only for the UK experience but also for future capital structure studies in general.